2015
DOI: 10.1063/1.4918387
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of twin-screw extrusion polymer melting: Common pitfalls and how to avoid them

Abstract: Abstract. The process for compounding engineered polymer formulations is comprised of several unit operations. These typically include, but are not limited to: feedstock introduction, polymer melt-mixing, distributive/dispersive mixing of minerals/fibers, removal of volatiles, and pressurization for discharge. While each unit operation has an impact on process productivity and the quality of the finished product, polymer melt-mixing has a significantly greater impact than the others. First, it consumes 50, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A polypropylene homopolymer (ELTEXP HV001PF, produced by INEOS Olefins & Polymers Europe) with density of 0.905 g/cm 3 and MFI = 10 g/10 minutes (2.16 kg, 190 C) was used in the experiments. The polymer was supplied in powder form, in order to avoid eventual clogging the multislit die, as explained below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polypropylene homopolymer (ELTEXP HV001PF, produced by INEOS Olefins & Polymers Europe) with density of 0.905 g/cm 3 and MFI = 10 g/10 minutes (2.16 kg, 190 C) was used in the experiments. The polymer was supplied in powder form, in order to avoid eventual clogging the multislit die, as explained below.…”
Section: Methodsmentioning
confidence: 99%
“…Melting is an important process stage, influencing the development of pressure and temperature along the screw axis, as well as accounting for at least 50% of the total energy consumption. [3] Experimental investigations have also shown that immiscible polymer blends and nanocomposites experience major changes of morphology (and of chemical conversion in the case of reactive extrusion) upon melting. [4][5][6] Melting is influenced by the local screw configuration (typically containing restrictive elements), by the physical form and properties of the feedstock and by the operating conditions (feeding rate, screw speed, barrel temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Since most heating occurs at the bed surfaces, this energy dissipation can create a surface film of melted polymer to be formed which would likely reduce the efficiency of the melting process unit operation screw configuration. [32] The solid bed is deformed and rearranged as the pellets travel through the nip region between the screws where additional frictional heating can occur at the pellet-pellet contact surfaces.…”
Section: Visualization and Measurement Of The Solids Transport Zonementioning
confidence: 99%
“…The selection of the appropriate configuration of the plasticising system can therefore be presented as a search for a compromise between the best mixing of components and the lowest possible degradation of components, especially polymers [11,12]. One way to avoid the impact is to crush commercially available granules of polymers to reach smaller grain sizes [1,13].…”
Section: Introductionmentioning
confidence: 99%